ATHLETICS, MEMORY, AND COMMUNITY IN HELLENISTIC AND ROMAN MESSENE. (11th June 2018) - PAPAKONSTANTINOU, ZINON
Abstract: Recent excavations in the site of Messene have unveiled numerous inscriptions from the Hellenistic and Roman imperial periods that significantly increase our understanding of the agonistic life of the city. By utilizing this new set of evidence in this paper I examine patterns of athletic competition by Messenian athletes in panhellenic and local contests. Moreover, I explore victory commemoration practices in the urban landscape of Messene as a means to comprehend how the community acted out, in an institutionalized manner, its collective memory, identity, and historical consciousness.